Wrestling injuries during the Tokyo 2020 olympic games - Shadgan, B.; Szabolcs, M.; Aaeva, E.; Masujima, A. (British Journal of Sports Medicine, 2021)
Background Understanding the incidence and characteristics of injuries in each sport helps to implement more effective preventive measures. Studying this information after the occurrence of the COVID-19 pandemic was particularly important. Accordingly, the medical commission of the United World Wrestling (UWW) has implemented a systematic surveillance of injuries during the Tokyo 2020 Olympic Games.